1996
DOI: 10.1079/bjn19960013
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipid fatty acids of brain and liver are modified by α-tocopherol and dietary fat in growing chicks

Abstract: Dietary fatty acids modify phospholipid fatty acids in brain and liver of growing chickens post-hatching. The effect of vitamin E deficiency on this process is unknown and may be relevant to the pathogenesis of chick nutritional encephalomalacia (NE). Therefore laying hens received a diet low in vitamin E (10 mg a-tocopherol/kg feed). Resulting chicks were assigned to nine dietary groups each fed with either oleic (18:ln-9, 58 g/kg), linoleic (18:2n-6, 57 g/kg) or linolenic (18:3n-3, 56 g/kg) acid together wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 32 publications
0
14
1
1
Order By: Relevance
“…decreased C18:1 and increased C20:1, increased C18:2, 20:4 and C22:4, decreased C18:3 and C22:6, the reasons for these effects are not clear. In contrast to our findings, the proportion of n-9 fatty acids in polar lipids of brain and liver of growing chickens was increased when 125 mg/kg of α-tocopheryl acetate was added to their diets (Fuhrmann and Sallman, 1996). On the other hand, in line with the findings of Lauridsen et al (1999), the increased concentrations of n-6 fatty acids, i.e.…”
Section: Fatty Acid In Egg Yolk Lipidscontrasting
confidence: 57%
“…decreased C18:1 and increased C20:1, increased C18:2, 20:4 and C22:4, decreased C18:3 and C22:6, the reasons for these effects are not clear. In contrast to our findings, the proportion of n-9 fatty acids in polar lipids of brain and liver of growing chickens was increased when 125 mg/kg of α-tocopheryl acetate was added to their diets (Fuhrmann and Sallman, 1996). On the other hand, in line with the findings of Lauridsen et al (1999), the increased concentrations of n-6 fatty acids, i.e.…”
Section: Fatty Acid In Egg Yolk Lipidscontrasting
confidence: 57%
“…Previous experiments conducted on growing chicks [41] showed that, in the liver, the unsaturation index of PL increased during vitamin E deficiency, whereas n-9 fatty acids (oleic acid) decreased.…”
Section: Discussionmentioning
confidence: 98%
“…FA concentrations were analysed by measuring fatty acid methyl esters via gas chromatography with di-C17-phosphatidylcholine as internal standard, as previously described[18,21]. Methyl esters were measured with a Varian CP 3800 gas chromatograph (Varian, Darmstadt, Germany) equipped with a flame ionization detector.…”
Section: Methodsmentioning
confidence: 99%